Odpad obogatitve pri prenehanju vzajemnih pogodb - Lutman, Karmen (Podjetje in delo, 2015)
The article analyses the consequences of void and rescinded contracts. It focuses on situations where a party of an invalid mutual contract has changed his position so that he is overall not enriched. Under German law, such cases are solved by the use of doctrine of the balance (Saldotheorie) or doctrine of two condictiones (Zweikondiktionenlehre), whereas this is covered by counter-restitution and change of position defences in English law. The first part of the article presents the institute of void contract, the process of rescission, and basis of German and English law of unjust(ified) enrichment. Both legal systems recognise the principle of enrichment so that a bona fide recipient is generally allowed to rely on disenrichment. However, due to the tie between performance and counter-performance, the disenrichment rule is restricted in case of an invalid mutual contract under some circumstances. In the second part, the author presents restitutional rules that apply to void and rescinded contracts under Slovenian law. The discussion is focused on the question, whether one party can rely on disenrichment, with the effect that one party must shift back its wealth while the other need not.
Keywords: pogodbe; pogodbeno pravo; prenehanje